2021
DOI: 10.1021/acsami.1c02963
|View full text |Cite
|
Sign up to set email alerts
|

Electron Doping Effect in the Resistive Switching Properties of Al/Gd1–xCaxMnO3/Au Memristor Devices

Abstract: We report on the resistive switching (RS) properties of Al/Gd 1– x Ca x MnO 3 (GCMO)/Au thin-film memristors. The devices were studied over the whole calcium substitution range x as a function of electrical field and temperature. The RS properties were found to be highly dependent on the Ca substitution. The optimal concentration was determined to be near x = 0.9, which is high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 45 publications
4
18
0
Order By: Relevance
“…The devices investigated are Al/Gd 0.1 Ca 0.9 MnO 3 (80 nm)/Au structures deposited on SrTiO 3 (STO) substrates by pulsed laser deposition (λ=308 nm from a XeCl-laser) [8]. The pulse duration was 25 ns (1500 pulses), with a repetition rate of 5 Hz, laser fluence of 2 J/cm 2 , and oxygen pressure of 0.175 Torr.…”
Section: Device Fabrication and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The devices investigated are Al/Gd 0.1 Ca 0.9 MnO 3 (80 nm)/Au structures deposited on SrTiO 3 (STO) substrates by pulsed laser deposition (λ=308 nm from a XeCl-laser) [8]. The pulse duration was 25 ns (1500 pulses), with a repetition rate of 5 Hz, laser fluence of 2 J/cm 2 , and oxygen pressure of 0.175 Torr.…”
Section: Device Fabrication and Measurementsmentioning
confidence: 99%
“…letter, we focus the attention on GCMO devices with x=0.9, which has been demonstrated to provide the highest resistance window [8]. It has also been observed that the Au and Al electrodes are associated with ohmic and rectifying contacts with the GCMO layer, respectively [8]. The devices exhibit asymmetrical switching voltages (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…We associate I 1 , I 2 , and I 3 with tunneling, Schottky-like, and soft-breakdown conduction, respectively [7][8][9][10][11][12]. Poole-Frenkel conduction is also a possibility which cannot be ruled out [8].  i , I 0i , and R i , i=1,2,3 are fitting parameters.…”
Section: Model Equationsmentioning
confidence: 99%
“…However, the potential use of these modern technologies is still facing issues, such as low data storage capacity, large power consumption, and low packing density, which need to be addressed [1,2] . Resistive memory devices are emerging as the cost‐effective alternative to overcome these challenges in modern technologies and capable of storing large data with better stability [3,4] . The first ever thin‐film based memory was proposed in 1963 by Cheng et al [2,5] .…”
Section: Introductionmentioning
confidence: 99%